Community institutions and natural resource governance in the Uttarakhand Himalaya - Mishra, Anil Kumar (New Delhi D. P. S. Publishing House, 2021)
Natural resources are recognized as the key of human wellbeing and survival and communities around the world have rapidly explored and utilized these resources. The sustainable utilization and management of natural resources were observed much later by the societies.
Keywords: Resources Sector; Governance; Himalaya Region